Composting as alternative for industrial wastes recycling - Gonçalves, Iuna Carmo Ribeiro; De Souza, Lusiene Barbosa; De Melo, Wanderley José [UNESP]; De Araújo, Ademir Sérgio Ferreira (My University, 2011)
Industrialization in the world has contributed for the increase in the generation of potentially toxic solid wastes. These wastes usually have high organic and inorganic content, including heavy metals. The most used method for disposal of industrial wastes is the sanitary sites, presenting a high risk of environmental contamination. Concerns about environmental quality have led to the introduction of alternative disposal methods such as the use as nutrient source for plants and as soil conditioners. Composting is an attractive alternative of industrial waste recycling. Application of this compost in agricultural soils can directly alter soil physicochemical properties as well as promote plant growth. In this short-communication, we summarize the importance and alternative of composting for industrial wastes recycling. © 2011 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Recycling; Soil; Tannery sludge; Textile sludge